Comparison of Ground Based Measurements of Solar UV Index with Satellite Estimation at Four Sites of Nepal - Sharma, Niranjan P; Bhattarai, Binod K; Sapkota, Balkrishna; Kjeldstad, Berit (Journal of the Institute of Engineering, 2012)
The main objective of this study is to compare the ground based measurements and satellite estimation of solar UV index in four sites namely, Kathmandu, Pokhara, Biratnagar and Lukla. Kathmandu (27.72°N, 85.32°E), Pokhara (28.22°N, 83.32°E) Biratnagar (26.45°N, 87.27° E) and Lukla ( 27.69°N, 86.73°E) and are located at an elevation of 1350m, 800m, 72m and 2850m respectively from the sea level. The ground based measurements and satellite estimation were performed by NILUUV irradiance meter and EOS Aura OMI satellite. The NILUUV irradiance meter is a six channel radiometer designed to measure hemispherical irradiances on a flat surface. The Ozone Monitoring Instrument (OMI) on board, the NASA EOS Aura space craft is a nadir viewing spectrometer that measures solar reflected and back scattered light in ultraviolet and visible spectrum. The study shows that OMI overestimate the ground based data before monsoon by 71.28%, 47.29%, 27.92% and 35.83% respectively at Kathmandu, Pokhara, Biratnagar and Lukla. However during the monsoon period the same comes down to 8.55%, 15.63%, 10.74%, and 11.33% respectively. The main reason behind these discrepancies might be due to the spatial resolution of the satellite which estimates the UV Index on the basis of 13×24 km2 in nadir where as the ground measurement is for a single point. The correlation between satellite derived and ground measured ozone column was found to be 91 % and 89% for Kathmandu and Lukla respectively. DOI: http://dx.doi.org/10.3126/jie.v8i3.5932 JIE 2011; 8(3): 58-71